2016
DOI: 10.1097/cmr.0000000000000214
|View full text |Cite
|
Sign up to set email alerts
|

BRAF inhibition for advanced locoregional BRAF V600E mutant melanoma

Abstract: Selective BRAF inhibitors (BRAFi) yield objective responses in 50% of patients with metastatic BRAF V600E mutant melanoma. Adding an MEK inhibitor increases this response rate to 70%. Limited data are available on the outcomes of unresectable stage III patients, and it remains unclear whether BRAF-targeted therapy can be utilized as a neoadjuvant strategy. Data on patients with advanced locoregional BRAF V600E mutant melanoma treated with BRAF-targeted therapy at Moffitt Cancer Center were analyzed to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 23 publications
2
28
2
Order By: Relevance
“…In this series BRAF inhibitor treatment led to fibrosis of tumor tissue and added a challenge to the surgical procedure itself; however, it did not lead to intraoperative complications in our series. This is compatible with previous reports which do not describe increased postoperative complications after BRAF inhibitor treatment [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this series BRAF inhibitor treatment led to fibrosis of tumor tissue and added a challenge to the surgical procedure itself; however, it did not lead to intraoperative complications in our series. This is compatible with previous reports which do not describe increased postoperative complications after BRAF inhibitor treatment [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 94%
“…Pathologic responses seen in the resected specimens were comparable to those in our series. The objective response rate was, however, lower, with only six out of 15 patients receiving surgical resection following BRAF inhibitor treatment [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their combined use (approved in 2014) has recently been shown in metastatic cases to provide a better complete response (CR) rate than Dabrafenib alone . The success of these novel inhibitors in systemically advanced disease was followed by case studies of locally advanced disease unsuitable for surgery which showed complete regression using either isolated BRAF inhibitor therapy with Vemurafenib or combined inhibitor therapy with Dabrafenib plus Trametinib . Up to now, irresectable stage III tumors where previously treated as stage IV disease, as no other recourse was available to achieve any kind of disease control.…”
Section: Discussionmentioning
confidence: 99%
“…The patient remained disease-free at 5-month follow-up [26]. In another case series of 15 patients, they observed a 70% response rate in patients with locally advanced melanoma; in addition six of the 15 patients underwent conversion from unresectable to resectable disease [27].…”
Section: Neoadjuvant Immunotherapymentioning
confidence: 91%